2005
DOI: 10.1111/j.1471-4159.2005.03347.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral entorhinal cortex lesions rearrange afferents, glutamate receptors, increase seizure latency and suppress seizure‐induced c‐fosexpression in the hippocampus of adult rat

Abstract: The entorhinal cortex (EC) provides the predominant excitatory drive to the hippocampal CA1 and subicular neurones in chronic epilepsy. Here we analysed the effects of one-sided lateral EC (LEC) and temporoammonic (alvear) path lesion on the development and properties of 4-aminopyridine-induced seizures. Electroencephalography (EEG) analysis of freely moving rats identified that the lesion increased the latency of the hippocampal seizure significantly and decreased the number of brief convulsions. Seizure-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 67 publications
(189 reference statements)
1
45
0
Order By: Relevance
“…The same study also found that reactive astrocytes maintained the domain organization after deafferentation of the dentate gyrus (Wilhelmsson et al, 2006). This injury model is only inconsistently associated with seizure pathology (Kopniczky et al, 2005), thus indirectly supporting the conclusion that loss of astrocytic domain organization is restricted to pathologies associated with EEG abnormalities.…”
Section: Discussionsupporting
confidence: 62%
“…The same study also found that reactive astrocytes maintained the domain organization after deafferentation of the dentate gyrus (Wilhelmsson et al, 2006). This injury model is only inconsistently associated with seizure pathology (Kopniczky et al, 2005), thus indirectly supporting the conclusion that loss of astrocytic domain organization is restricted to pathologies associated with EEG abnormalities.…”
Section: Discussionsupporting
confidence: 62%
“…When processing the images, each was treated identically to allow comparison of pixel densities in different hippocampal and cortical regions. The pixel density of immunoreactivity was measured by an experimenter blind to the experimental conditions using a previously established quantification strategy (Kopniczky et al, 2005). Briefly, open circular cursors with a diameter of 0.30 mm were placed on the striatum (eight circles) and perirhinal cortex (four circles; as illustrated in Fig.…”
Section: Histoblot Analysis Of Ampa and Nmda Receptor Protein Expressionmentioning
confidence: 99%
“…Brains from three wild-type (mGluR7 ϩ/ϩ ) and three mGluR7-deficient transgenic (mGluR7 Ϫ/Ϫ ) adult mice were used to determine changes in the distribution of AMPA-and NMDA-type ionotropic glutamate receptor (iGluR) subunit proteins, using an in situ blotting technique (histoblot) (Kopniczky et al, 2005). In brief, animals were deeply anesthetized and decapitated, and the brains were quickly frozen in isopentane and stored at Ϫ80°C until sectioning.…”
Section: Histoblot Analysis Of Ampa and Nmda Receptor Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dentate gyrus subfield of the hippocampus is particularly susceptible to seizures, and appears to be the primary locus of temporal lobe epilepsy. The vulnerability of the dentate gyrus to seizures may result from disrupted GABAergic synaptic transmission as the pathological changes that occur in the dentate during epilepsy include loss of GABAergic inhibitory interneurons [44][45][46] and sprouting of axons [47][48][49]. Synchronization, characteristic of epileptiform bursts, has been recorded in the hippocampus, and has been theorized to be mediated by electrical coupling via GJs [50].…”
Section: Introductionmentioning
confidence: 99%